Pengembangan Modul Pembelajaran IPA Kelas V dengan Metode SQ3R untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa di SDN Inpres Kala - Amikratunnisyah; Siti Fatonah (Postgraduate, University of Mataram, 2023)
This study aims to Produce Class V Science learning modules using the SQ3R method as learning media, Describe the feasibility of Class V Science learning modules, and Analyze the effectiveness of implementing Science learning modules prepared using the SQ3R method in improving reading skills understanding of fifth grade students at SDN Inpres Kala, Bima Regency. This research is an ADDIE model development research. The results of this research resulted in even semester Class V Science learning modules compiled using the SQ3R method (survey, question, read, recite, and review). The module has been validated by experts and has the criteria of being very suitable for use as a learning medium with the eligibility percentage of media experts 98%, material experts 95%, linguists 94%, practitioners 96%, and peer review 92%, and a very good response from teachers by 85%, and 90% students. Science learning modules prepared using the SQ3R method can improve students reading comprehension skills, this is obtained based on the results of hypothesis testing paired sample t-test with result themselves. 2 tailed of 0.000 <0.05, and with a mean-value comparison pretest 42.64 and posttes 55.27. From these results it can be concluded that students reading skills experienced a significant increase.